A Bright Light at the End of the Tunnel: Factors Associated With Complete Mental Health After a Suicide Attempt. Issue 4 (2nd October 2022) - Fuller-Thomson, Esme; Baiden, Philip; Mahoney, Ian P.; MacNeil, Andie
Abstract: Objective: The aim of this study was to investigate factors associated with complete mental health (CMH) among a nationally representative sample of Canadians who had a history of suicide attempts. Methods: Data for this study came from the 2012 Canadian Community Health Survey–Mental Health. A subsample of 796 respondents who had ever attempted suicide was analyzed. The outcome variable investigated was CMH, which includes three elements: (a) absence of past-year suicidality or mental illness (measured by the World Health Organization version of the Composite International Diagnostic Interview); (b) happiness or satisfaction; and (c) social and psychological well-being. Bivariate analyses and binary logistic regression were conducted to identify factors associated with CMH among Canadians who had a history of suicide attempts. Results: Of the 796 respondents who had a history of suicide attempts, 28.4% were in CMH. In accordance with past research, positive factors associated with CMH were as follows: having a confidant, lacking chronic pain, absence of insomnia, being female, older age, higher income, and having no history of mental illness, including bipolar disorder, major depressive episode, or generalized anxiety disorder. Those with two suicide attempts were less likely to experience CMH than those with one suicide attempt. Surprisingly, medical attention after the attempt was positively associated with CMH. In total, these factors accounted for 29% of the variance in CMH. Conclusions: Adults with a history of suicide attempts can achieve an excellent level of mental health. These findings suggest that interventions to promote social support and manage chronic pain and insomnia may be helpful. HIGHLIGHTS: More than one in four adults with a history of suicide attempts are in complete mental health Having a confidant was positively associated with having complete mental health after suicide attempt Those with a history of suicide attempts need ongoing mental health support